Application of a Low-dissipation HLLD Approximate Riemann Solver to Solar Wind Simulations - Caixia Li; Zhenning Shen; Man Zhang; Xueshang Feng (The Astrophysical Journal)
We investigate the steady-state solar wind in spherical coordinates using a low-dissipation Harten–Lax–van Leer-Discontinuities Riemann solver, in which the magnetic field is decomposed into an initial potential field B _0 and a time-dependent part B _1 . A constrained transport method is employed to effectively preserve the divergence-free condition, with the relative divergence errors maintained at truncation level throughout the simulation. The solar wind plasma and magnetic field equations are solved using a one-step MUSCL-type time integration scheme, combined with spacetime reconstruction at cell interfaces and edges. Prior to the solar wind simulation, the accuracy and robustness of the numerical method are verified through benchmark tests, including the smooth Alfvén wave problem, the Mach 800 dense MHD jet, and the MHD blast wave in spherical polar coordinates. The results confirm that the scheme achieves second-order accuracy and remains stable under challenging physical conditions. The validated scheme is then applied to simulate the structured solar wind during Carrington Rotation 2236, using Helioseismic and Magnetic Imager 720 s cadence line-of-sight magnetograms as input. The simulation successfully reproduces key large-scale solar wind features, such as polar and extended coronal holes, open and closed magnetic field regions, helmet streamers, pseudo-streamers, the heliospheric current sheet, and the spatial distribution of fast and slow solar wind streams. Comparisons with remote sensing observations and in situ measurements demonstrate reasonable agreement. However, discrepancies remain in the temporal variations of plasma parameters and the detailed structure of coronal holes, suggesting areas for further model refinement.